Go essentials a practical guide to Concurrency, gRPC, and more - Percival, Rob (Packt Publishing, 2024)
Dive into the world of Go programming with a structured course that takes you from the fundamentals to advanced techniques. You'll begin by understanding the core concepts such as variables, loops, functions, and pointers. As you progress, you'll explore more complex topics like structs, interfaces, and error handling, which are essential for writing robust Go code. In the intermediate sections, you'll delve deeper into Go's unique features, like goroutines and channels, which enable you to write concurrent programs. You'll also learn about testing in Go, using mutexes, and working with generics. The course provides a balanced mix of theory and practice, ensuring you can apply what you learn immediately. By the end of the advanced section, you'll have a solid grasp of Go's concurrency model, allowing you to build high-performance applications. The final part of the course introduces you to gRPC, a powerful framework for remote procedure calls. You'll learn how to set up a gRPC server and client and implement gRPC in your Go applications. Additionally, the course touches on the Gin framework, giving you a complete toolkit for modern Go development. With this comprehensive training, you'll be equipped to tackle any Go programming challenge confidently.